Response and recovery of microbial communities subjected to oxidative and biological treatments of 1, 4-dioxane and co-contaminants. (1st February 2019) - Miao, Yu; Johnson, Nicholas W.; Gedalanga, Phillip B.; Adamson, David; Newell, Charles; Mahendra, Shaily
Abstract: Microbial community dynamics were characterized following combined oxidation and biodegradation treatment trains for mixtures of 1, 4-dioxane and chlorinated volatile organic compounds (CVOCs) in laboratory microcosms. Bioremediation is generally inhibited by co-contaminate CVOCs; with only a few specific bacterial taxa reported to metabolize or cometabolize 1, 4-dioxane being unaffected. Chemical oxidation by hydrogen peroxide (H2 O2 ) as a non-selective treatment demonstrated 50–80% 1, 4-dioxane removal regardless of the initial CVOC concentrations. Post-oxidation bioaugmentation with 1, 4-dioxane metabolizer Pseudonocardia dioxanivorans CB1190 removed the remaining 1, 4-dioxane. The intrinsic microbial population, biodiversity, richness, and biomarker gene abundances decreased immediately after the brief oxidation phase, but recovery of cultivable microbiomes and a more diverse community were observed during the subsequent 9-week biodegradation phase. Results generated from the Illumina Miseq sequencing and bioinformatics analyses established that generally oxidative stress tolerant genus Ralstonia was abundant after the oxidation step, and Cupriavidus, Pseudolabrys, Afipia, and Sphingomonas were identified as dominant genera after aerobic incubation. Multidimensional analysis elucidated the separation of microbial populations as a function of time under all conditions, suggesting that temporal succession is a determining factor that is independent of 1, 4-dioxane and CVOCs mixtures. Network analysis highlighted the potential interspecies competition or commensalism, and dynamics of microbiomes during the biodegradation phase, in line with the shifts of predominant genera and various developing directions during different steps of the treatment train. Collectively, this study demonstrated that chemical oxidation followed by bioaugmentation is effective for treating 1, 4-dioxane, even in the presence of high levels of CVOC mixtures and residual peroxide, a disinfectant, and enhanced our understanding of microbial ecological impacts of the treatment train. These results will be valuable for predicting treatment synergies that lead to cost savings and improved remedial outcomes in short-term active remediation as well as long-term changes to the environmental microbial communities. Graphical abstract: Image 1 Highlights: Groundwater/soil microbial community was altered after oxidation and biodegradation. After exposure to H2 O2 and CVOCs, bioaugmented CB1190 can metabolize 1, 4-dioxane. Dynamics of microbial populations varied along with different treatment stages. Many taxa exhibited resilience against peroxide exposure and subsequently recovered. Metagenomic analysis will be valuable for long-term management of polluted sites.